THE MEMORIZE-SPEAK UP-HABITUATION METHOD AS AN EFFORT TO IMPROVE THE MASTERY OF FOREIGN LANGUAGE SKILLS - Abd. Hamid Wahid; Fathor Rozi; Hasan Baharun; Santi Laili Safitri (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract:This study aimed to analyze and examine the MSH (Memorize-Speak Up-Habituation) method on foreign language mastery skills, especially English. This research used a descriptive qualitative approach with case study research at the LIPs (Language Intensive Program of Boarding Junior High School of Nurul Jadid) Paiton, Probolinggo. The instruments used were observation, in-depth interviews, and documentation to support the completeness of the data. The data analysis technique was carried out through the stages of data collection, data reduction, data presentation, and conclusion of research results. The findings indicated that the MSH method was applied with the stages of Memorizing new vocabulary and pronunciation, Speak Up, or integrating the use of new vocabulary in speaking activities, and habituation of foreign language activities. This study shows the implication that with the MSH method, LIPs members can master 4 English skills (listening, writing, reading, and speaking) correctly even though it requires high discipline.Abstrak:Penelitian ini bertujuan untuk menganalisis serta mengkaji penggunaan metode MSH (Memorize-Speak Up-Habituation) terhadap keterampilan penguasaan berbahasa asing, khususnya bahasa Inggris. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian studi kasus di lembaga LIPs (Language Intensive Program of SMP Nurul Jadid) Paiton, Probolinggo. Instrumen dalam penelitian ini mengunakan observasi dan wawancara mendalam serta dokumentasi untuk mendukung kelengkapan data. Teknik analisis data pada penelitian ini dilakukan dengan tahap pengumpulan data, reduksi data, penyajian data, dan penyimpulan hasil penelitian. Hasil penelitian menunjukkan bahwa metode MSH diterapkan dengan tahapan Memorize (mengingat) kosakata baru serta pelafalannya; Speak Up (berbicara) atau mengintegrasikan penggunaan kosakata baru dalam kegiatan speaking (berbicara); dan Habituation (pembiasaan) kegiatan berbahasa asing. Penelitian ini menunjukkan implikasi bahwa dengan metode MSH, anggota LIPs dapat menguasai 4 kompetensi bahasa Inggris (listening, writing, reading, speaking) dengan tepat walau membutuhkan kedisiplinan tinggi.